Toxoplasmosis and Cerebral Toxoplasmosis in HIV/AIDS Patients in Kariadi Hospital, Semarang - Dauda Sanni Hassana; Suharyo Hadisaputro; Muchlis Achsan Udji Sofro (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2021)
Background: Toxoplasmosis is an infection caused by Toxoplasma gondii which affects the central nervous system resulting to a fatal situation in HIV patients especially at the advanced stage. Cerebral toxoplasmosis (CT) is the clinical presentation of toxoplasmosis in individuals with HIV/AIDS. The study was carried to describe the prevalence of toxoplasmosis and cerebral toxoplasmosis in HIV/AIDS patients attending the hospital setting used in the study.Methods: Patients medical records were checked and analyzed for demographic characteristics as well as to determine the results of toxoplasma IgG tests for HIV/AIDS patients as well as those who had cerebral toxoplasmosis. The study was a descriptive study.Results: Out of the 158 HIV/AIDS patients tested, 129 (81.6%) were positive for T. gondii. A 62.0% prevalence rate was recorded for the male subjects while 19.6% prevalence rate was recorded for the female subjects although there was no significant difference (X2=0.58, P > 0.05). 69.3% of the total population studied had cerebral toxoplasmosis with a prevalence rate of 74.3% and 25.3%) in male and female respectively. A higher prevalence was recorded from the age group >30years without significant difference (X2=0.74, P > 0.05).Conclusion: More research is required to know the exact prevalence of the parasite in this group of individuals since not all the patients were tested.